(untitled) (Academic Journal of Internal Affairs, 2023)
Aim: Within government activities, we have seen a marked digitalisation process in the last few years, both at domestic and international level. In this environment, human activity is naturally replaced by software solutions, and this is true for the governmental interaction with clients through government platforms. The aim of this study is to explore the conditions for the use of chatbot communication forms in public administrations, by examining the case where a government platform is used for the administrative procedures. The study also aims to explore and systematise the impact of these solutions on the transparency of the government platform and the administrative procedures carried out through it. Methodology: Critically analyse national and European legal sources of the subject, as well as implemented and planned practical solutions, in order to formulate a set of requirements and recommendations. Findings: The set of requirements for administrative procedures identifies a number of requirements that can be interpreted in the context of the use of chatbots as a communication method. These can also be interpreted in terms of legal compliance, and are not just recommendations or good practices. The impact of a software solution on transparency is twofold: on the one hand, it can greatly increase the transparency of the platform and the process, due to its speed and interactivity, and on the other hand, it can reduce it, depending on the degree of IT sophistication. Value: The most important new knowledge of the study, which can be interpreted in scientific terms, is that it defines the administrative requirements for chatbots as software solutions based on artificial intelligence, when they are used for the administration and communication of administrative procedure via government platforms. An important new concept of the study is the establishment of the equivalence principle, which applies when the human administrator’s contact and information tasks are replaced by a software solution on the platform in their entirety, without any choice.